Alginate oligosaccharide extends the service lifespan by improving the sperm metabolome and gut microbiota in an aging Duroc boars model - Zhou, Yexun; Wei, Zeou; Tan, Jiajian; Sun, Haiqing; Jiang, Haidi; Gao, Yang; Zhang, Hongfu; Schroyen, Martine (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Alginate oligosaccharide (AOS), as a natural non-toxic plant extract, has been paid more attention in recent years due to its strong antioxidant, anti-inflammatory, and even anti-cancer properties. However, the mechanism by which AOS affects animal reproductive performance is still unclear. Methods The purpose of this study is to use multi-omics technology to analyze the effects of AOS in extending the service lifespan of aging boars. Results The results showed that AOS can significantly improve the sperm motility (p < 0.05) and sperm validity rate (p < 0.001) of aging boars and significantly reduce the abnormal sperm rate (p < 0.01) by increasing the protein levels such as CatSper 8 and protein kinase A (PKA) for semen quality. At the same time, AOS significantly improved the testosterone content in the blood of boars (p < 0.01). AOS significantly improved fatty acids such as adrenic acid (p < 0.05) and antioxidants such as succinic acid (p < 0.05) in sperm metabolites, significantly reducing harmful substances such as dibutyl phthalate (p < 0.05), which has a negative effect on spermatogenesis. AOS can improve the composition of intestinal microbes, mainly increasing beneficial bacteria Enterobacter (p = 0.1262) and reducing harmful bacteria such as Streptococcus (p < 0.05), Prevotellaceae_UCG-001 (p < 0.05), and Prevotellaceae_NK3B31_group (p < 0.05). Meanwhile, short-chain fatty acids in feces such as acetic acid (p < 0.05) and butyric acid (p < 0.05) were significantly increased. Spearman correlation analysis showed that there was a close correlation among microorganisms, sperm metabolites, and sperm parameters. Discussion Therefore, the data indicated that AOS improved the semen quality of older boars by improving the intestinal microbiota and sperm metabolome. AOS can be used as a feed additive to solve the problem of high elimination rate in large-scale boar studs.